Peningkatan Kreativitas Dan Kesadaran Lingkungan Anak Melalui Pelatihan Ecoprint Di Kp. Solodengeun Panimbang Jaya - Umaya, Siti; Ardiansyah, Rizqi; Dwiki Putra Aryono, Gagah; Purnama, Andika; Kohar, Abdul (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2025)
Environmental awareness is one of the important aspects that need to be instilled from an early age, because children are the next generation who will face ecological challenges in the future. One creative approach that can be used is ecoprint training, which is a technique of printing patterns on fabrics by utilizing natural leaves, flowers, and plants around the environment. This study aims to see how ecoprint training can increase creativity while fostering environmental awareness in children in Solodengeun Village, Panimbang Jaya Village. The method used is qualitative descriptive with stages of activities in the form of preparation, socialization, demonstration, direct practice, and evaluation. Data was collected through observation, documentation, and brief interviews with participants. The results of the activity showed that the children followed each stage with great enthusiasm. They are not only able to produce unique works of art from natural materials, but also understand the important value of taking care of the environment through the wise use of resources. This activity has been proven to foster curiosity, improve motor skills, train creativity, and instill ecological values in a fun way. Overall, ecoprint training has proven to be effective as a holistic learning medium that combines art, creativity, and environmental education. This program not only provides a memorable learning experience, but also forms an eco-friendly character from an early age. Thus, ecoprints deserve to be developed more widely in schools and communities as an alternative strategy in instilling environmental awareness while honing children's creativity. Keywords: ecoprint, children's creativity. Environmental education, ecological awareness